PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN MELALUI REKRUTMEN TENAGA PENDIDIK DI SD ISLAM ABU DZAR TANGERANG SELATAN - Ria Anggreini (UNISAN JURNAL, 2023)
The purpose of this study was to determine the role of the principal in the recruitment of educators. This study uses a qualitative approach with descriptive qualitative methods. The respondents were the principal, vice principal of the curriculum section and several teachers. Data collection techniques used are interview, observation, and documentation studies. After the data is collected, data processing is carried out by analyzing the existing data, then interpreted by referring to the research framework. The results showed that the role of school principals in improving the quality of education through the recruitment of educators was quite good. This recruitment activity begins with planning, organizing, implementing and finally placing. The method used is quite effective for the institution, this is proven by the fact that there are no teachers who are negligent in their duties, as stated by the principal as the head of recruitment and decision making in the recruitment of prospective educators is carried out by discussing with the team first.